2020
DOI: 10.1111/eci.13387
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and prognosis of hospitalized COVID‐19 patients with incident sustained tachyarrhythmias: A multicenter observational study

Abstract: Introduction: Little is still known about the prognostic impact of incident arrhythmias in hospitalized patients with COVID-19. The aim of this study was to evaluate the incidence and predictors of sustained tachyarrhythmias in hospitalized patients with COVID-19, and their potential association with disease severity and in-hospital mortality. Materials and methods: This was a retrospective multicenter observation study including consecutive patients with laboratory confirmed COVID-19 admitted to emergency dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
75
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 56 publications
(79 citation statements)
references
References 18 publications
1
75
2
1
Order By: Relevance
“…A low prevalence of coexisting cardiovascular comorbidities, such as coronary artery disease, chronic kidney disease and atrial fibrillation, accounting for less than 4%, has been reported among COVID-19 patients not requiring hospitalization, which is different than those reported by cohort studies in hospital settings (ranging from 5 to 17%) [ 2 , 12 , 13 ]. This finding might be explained by the recommendation to refer COVID-19 patients with a low ischemic threshold related to underlying cardiovascular disease, who were at increased risk to develop myocardial injury or a clinically severe form of the disease and death [ 14 ], to emergency departments.…”
Section: Discussionmentioning
confidence: 91%
“…A low prevalence of coexisting cardiovascular comorbidities, such as coronary artery disease, chronic kidney disease and atrial fibrillation, accounting for less than 4%, has been reported among COVID-19 patients not requiring hospitalization, which is different than those reported by cohort studies in hospital settings (ranging from 5 to 17%) [ 2 , 12 , 13 ]. This finding might be explained by the recommendation to refer COVID-19 patients with a low ischemic threshold related to underlying cardiovascular disease, who were at increased risk to develop myocardial injury or a clinically severe form of the disease and death [ 14 ], to emergency departments.…”
Section: Discussionmentioning
confidence: 91%
“…However, the incidence and nature of atrial arrhythmias among patients with SARS-CoV-2 was poorly documented. Newly published studies suggest that the most frequent incident sustained arrhythmia is AF in the hospitalized COVID-19 population [ 18 ]. Abrams et al retrospectively described clinical characteristics and compared factors contributing toward arrhythmic versus non-arrhythmic death in patients with COVID-19 [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a series of 414 patients hospitalized with COVID-19, Russo et al studied potential association of sustained tachyarrhythmias with disease severity and in-hospital death. The results of this study suggest that AF was not associated with mortality [ 18 ]. Elias et al analyzed 1258 patients and identified only 42 incident AF or AFL events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arrhythmias are complex and multifactorial in a COVID-19 patient and may result from metabolic derangements, hypoxia, acidosis, intravascular volume imbalances, neurohormonal, and catecholaminergic stress. 4 , 5 Sepsis is characterized by a systemic process involving inflammatory cytokines and autonomic dysfunction. Postulated mechanisms of this arrhythmogenesis include autonomic nervous system-induced calcium entry into cardiac myocytes, spontaneous release of calcium from the sarcoplasmic reticulum, 6 as well as possible direct LA injury due to coronary artery disease with small vessel thrombosis.…”
mentioning
confidence: 99%